Implementation and application of automata 15th international conference, CIAA 2010, Winnipeg, MB, Canada, August 12-15, 2010. revised selected papers - Domaratzki, Michael; Salomaa, Kai (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed papers of the 15th International Conference on Implementation and Application of Automata, CIAA 2010, held in Manitoba, Winnipeg, Canada, in August 2010.The 26 revised full papers together with 6 short papers were carefully selected from 52 submissions. The papers cover various topics such as applications of automata in computer-aided verification; natural language processing; pattern matching, data storage and retrieval; bioinformatics; algebra; graph theory; and foundational work on automata theory.